Radical Deprivation on Trial The Impact of Judicial Activism on Socioeconomic Rights in the Global South - Rodríguez Garavito, César ca. 20./21. Jh (Comparative Constitutional Law and Policy, 2015)
This book is an empirical study of contributions by courts in the Global South to comparative constitutionalism. It offers an analytical framework for understanding these constitutional innovations and illustrates them with a qualitative study of the most ambitious case in constitutional adjudication in Latin America over the last decade: the Colombian Constitutional Court's structural injunction affecting the rights of over five million internally displaced people and its implementation process. Although the ruling (known as T25) was handed down in 2004, its monitoring process continues. This book traces the case's evolution from its origin to its effects on policy, politics and public opinion. It also compares the implementation and effects of T25 with those of other rulings on the rights to health, food, housing, and prison overcrowding in Colombia, India and South Africa. The study's insights will be of interest to scholars of comparative constitutionalism in Latin America, Africa and Asia